Voice: A Primordial Tool in the Training of Young Horses - Porcher, Jocelyne; Barreau, Sophie (Humanimalia, 2023)
The role of voice in work relations with horses has been little studied. However, the results of the research we conducted into the professional training of young horses, shows that equestrians’ use of voice dominates training. Our results demonstrate a specific tessitura in the voices of the equestrians (from medium to medium-low), as well as a ternary rhythm in the voices of the most experienced among them. This results of our exploratory study confirm the interest of studying the role of voice in the construction of an interspecies tie between humans and horses, and the place of affectivity at work.